Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
D
Step-by-step explanation:
f(x) = 3x - 12
f(2) = 3(2) - 12
= 6 - 12
= -6
Answer:
The answer is -6
Step-by-step explanation:
f(x) = 3x - 12; f(2)
f(2) = 3x - 12
f(2) = 3(2) - 12
f(2) = 6 - 12
f(2) = -6
Thus, The answer is -6
-TheUnknownScientist
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.